Utilization of Communication Models To Improve Implementation of Public Information Disclosure in Cirebon District Government - Irawan Irawan; Marwan Marwan; Sigit Purnomo (Dinasti Publisher, 2025)
Transparency of information is a responsibility that must be given by the government. Crucial problems that cause PPID to not function properly. The purpose of this study is to determine the Communication Model to Improve the Implementation of Public Information Transparency in the Cirebon Regency Government . This study uses a qualitative method that is normative and empirical, with research that examines communication models, with data collection techniques carried out through triangulation of Documentation, In-depth Interviews , Direct Observation, with Research Instruments . The results of this study The use of effective communication models has a strategic role in improving the implementation of public information disclosure in the Cirebon Regency Government. With the right communication approach, the government can encourage transparency and accountability in delivering information to the public. The communication model used must be adjusted to the social an cultural characteristics of the local community so that the message conveyed can be received and understood well. The use of information and communication technology (ICT) is an important element in expanding public access to public information. Adequate ICT infrastructure and competent human resources are needed to ensure smooth information management. In addition, two-way communication between the government and the community needs to be improved so that participatory interactions occur in public policy making. Overall, the use of effective communication models can narrow the information gap between the government and the community, increase citizen awareness of their rights and obligations, and encourage active involvement in the government process. This will ultimately strengthen the quality of public services and build public trust in the Cirebon Regency Government.